Study of Intravenous Single-Dose Toxicity Test of Bufonis venonum Pharmacopuncture in Sprague-Dawley Rats - Ki-Rok Kwon; Jun-Sang Yu; Seung-Ho Sun; Kwang-Ho Lee (Korean Pharmacopuncture Institute, 2016)
Objectives: Bufonis venonum (BV) is toad venom and is the dried, white secretions of the auricular and the skin glands of toads. This study was performed to evaluate the toxicity of intravenous injection of Bufonis venonum pharmacopuncture (BVP) through a single-dose test with sprague-dawley (SD) rats. Methods: Twenty male and 20 female 6-week-old SD rats were injected intravenously in the caudal vein with BVP or normal saline. The animals were divided into four groups with five female and five male rats per group: the control group injected with normal saline, the low-dosage group injected with 0.1 mL/animal of BVP, the medium-dosage group injected with 0.5 mL/animal of BVP and the high-dosage group injected with 1.0 mL/animal of BVP. We performed clinical observations every day and body weight measurements on days 3, 7 and 14 after the injection. We also conducted hematology, serum biochemistry, and histological observations immediately after the observation period. Results: No mortalities were observed in any experimental group. Paleness occurred in the medium- and the high-dosage groups, and congestion on tails was observed in females in the medium- and the high-dosage groups. No significant changes in weight, hematology, serum biochemistry, and histological observations that could be attributed to the intravenous injection of BVP were observed in any experimental group. Conclusion: The lethal dose of intravenously-administered BVP in SD rats is over 1.0 mL/animal.